Chemosensory Gene Expression for Two Closely Relative Species Rhodnius robustus and R. prolixus (Hemiptera, Reduviidade, Triatominae) Vectors of Chagas Disease - Marchant, Axelle; Mougel, Florence; Jacquin-Joly, Emmanuelle; Almeida, Carlos E.; Blanchet, Denis; Bérenger, Jean-Michel; da Rosa, João A. [UNESP]; Harry, Myriam (Frontiers, 2021)
Two closely related species, Rhodnius prolixus and Rhodnius robustus, are the vectors of Trypanosoma cruzi, which is the causative agent of Chagas disease, but clearly exhibit clear-cut differences in their ecological behavior. R. prolixus is considered as a domiciliated species, whereas R. robustus only sporadically visits human houses in Amazonia. We performed a chemosensory gene expression study via RNA-sequencing (RNA-seq) for the two species and also included a laboratory introgressed R. robustus strain. We built an assembled transcriptome for each sample and for both sexes and compiled all in a reference transcriptome for a differential gene expression study. Because the genes specifically expressed in one condition and not expressed in another may also reflect differences in the adaptation of organisms, a comparative study of the presence/absence of transcripts was also performed for the chemosensory transcripts, namely chemosensory proteins (CSPs), odorant-binding proteins (OBPs), odorant receptors (ORs), gustatory receptors (GRs), and ionotropic receptors (IRs), as well as takeout (TO) transcripts because TO proteins have been proposed to be associated with chemosensory perception in both olfactory and taste systems. In this study, 12 novel TO transcripts from the R. prolixus genome were annotated. Among the 199 transcripts, out of interest, annotated in this study, 93% were conserved between R. prolixus and the sylvatic R. robustus. Moreover, 10 transcripts out of interest were specifically expressed in one sex and absent in another. Three chemosensory transcripts were found to be expressed only in the reared R. prolixus (CSP19, OBP9, and OR89) and only one in sylvatic R. robustus (OR22). A large set of transcripts were found to be differentially expressed (DE) between males and females (1,630), with a majority of them (83%) overexpressed in males. Between environmental conditions, 8,596 transcripts were DE, with most (67%) overexpressed in the sylvatic R. robustus samples, including 17 chemosensory transcripts (4 CSPs, 1 OBP, 5 ORs, 1 GR, 4 IR, and 2 TO), but 4 genes (OBP19, OR13, OR40, and OR79) were overexpressed in the reared samples.
Keywords: Chagas disease; chemosensory proteins (CSP); differential expression; GR); odorant and gustatory receptors (OR; odorant binding protein (OBP); Rhodnius prolixus; Rhodnius robustus